Analisis Kesiapan Penerapan Sistem Berbasis Elektronik (SPBE) dalam Pelayanan E-KTP Studi pada Dinas Kependudukan dan Pencatatan Sipil di Kabupaten Lebak - Rani Anggreini Dewi; Aliyah Aliyah; Mahriva Elda Azhani; Nurul Hotimah; Firya Al Nabillah; Reza Damayanti (INDO PUBLISHING, 2026)
Digital transformation in public administration has prompted various public agencies to adopt electronic systems, including in civil registration services. This study aims to examine the readiness of the Lebak Regency Population and Civil Registration Office to implement the Electronic-Based Government System (SPBE) for e-ID card services. The study was conducted using a descriptive qualitative approach with data collection techniques including field observations, in-depth interviews, and document analysis. Data analysis followed the interactive model by Miles, Huberman, and Saldana (2014), which encompasses data condensation, data presentation, and the drawing and verification of conclusions. The research findings indicate that the level of SPBE readiness within the agency is not uniform across all dimensions examined. The regulatory and policy framework is the strongest aspect, supported by a tiered legal framework ranging from the national to the local level. Leadership commitment and digital service innovations that have been in place since 2020 also serve as positive organizational assets. On the other hand, the limited number of civil servants, the suspension of formal training due to budget cuts, and the limited reach of digital services to the public remain challenges that require serious attention. Data indicates that out of approximately 1,500,000 residents, only about 1% are registered as users of online services, suggesting that the information gap is far more significant than the technological gap itself. This study recommends strengthening human resource capacity, optimizing infrastructure development budgets, and intensifying public communication as priority steps toward a more inclusive and equitable implementation of the SPBE.